2021
DOI: 10.1017/s1368980021001889
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in the impact of the COVID-19 pandemic on food sufficiency in California, April–July 2020: implications for food programmes and policies

Abstract: Objective: To evaluate regional differences in factors associated with food insufficiency during the initial months of the COVID-19 pandemic among three major metropolitan regions in California, a state with historically low participation rates in the Supplementation Nutrition Assistance Program, the nation’s largest food assistance program. Design: Analysis of cross-sectional data from Phase 1 (April 23 – July 21, 2020) of the U.S. Census Household Pulse Survey, a weekly national online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Cross-sectional research has identified factors associated with a higher risk for food insecurity and food insufficiency among U.S. adults during the pandemic, including being on low income, belonging to race and ethnic minorities, and having children in the household (23) , as well as differences in risk across geographic areas (e.g. urban v. rural, and metropolitan regions within a state) (24,25) . One drawback of cross-sectional studies is that the temporal direction of findings remains unclear.…”
Section: Food Insecurity In the Context Of The Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-sectional research has identified factors associated with a higher risk for food insecurity and food insufficiency among U.S. adults during the pandemic, including being on low income, belonging to race and ethnic minorities, and having children in the household (23) , as well as differences in risk across geographic areas (e.g. urban v. rural, and metropolitan regions within a state) (24,25) . One drawback of cross-sectional studies is that the temporal direction of findings remains unclear.…”
Section: Food Insecurity In the Context Of The Covid-19 Pandemicmentioning
confidence: 99%
“…urban v . rural, and metropolitan regions within a state) ( 24 , 25 ) . One drawback of cross-sectional studies is that the temporal direction of findings remains unclear.…”
Section: Food Insecurity In the Context Of The Covid-19 Pandemicmentioning
confidence: 99%
“…According to Rubin's classification on missing data, the data are missing at random (MAR) in our study because the probability to be included relates to some known property [33], namely respondents' socio-demographics. Following some recent studies which used HPS data [1,6,7], we applied the listwise deletion method and included the respondents with complete data in analysis. To address any potential nonresponse bias, the HPS recommended sampling weight was applied to all analyses in this study to reflect the representative proportion in the U.S. population [1,6,35].…”
Section: Study Design Settings and Participantsmentioning
confidence: 99%
“…Following some recent studies which used HPS data [1,6,7], we applied the listwise deletion method and included the respondents with complete data in analysis. To address any potential nonresponse bias, the HPS recommended sampling weight was applied to all analyses in this study to reflect the representative proportion in the U.S. population [1,6,35]. In addition, a power analysis was performed for the logistic regression analysis with the equation given by Hsieh, Bloch, and Larsen [36].…”
Section: Study Design Settings and Participantsmentioning
confidence: 99%
See 1 more Smart Citation